بلاغةالسخرية وفن إدارة الأزمات: The Rhetoric of Irony and The Art of Management Crisis - Samira Maslouhi (Universitas Ahmad Dahlan, 2022)
Analyzing and studying irony style in the daily life of individuals is of great importance due to the diversity of its topics and their intertwining, especially with the great influx and popularity caused by the spread of the Corona pandemic in a torrent of satirical discourse, such as jokes, funny video clips, cartoons, and others. In an attempt to address the state of panic and exaggeration that accompanied the emergence of the epidemic and the parallel discourse in the media, it is not an ordinary discourse produced by one individual but rather a cumulative discourse of social memory extended over time, in which the past overlaps with the present, thus forming a vessel for a cultural heritage that distinguishes a society and predicts its representations and opinions. And his attitudes towards different topics in his daily life or specific topics (educational, political, religious-, or some social phenomena. Irony in all its forms has been very popular. It has been popular with the public that every person has become a media device in itself, so it is enough to broadcast and publish pictures of senior officials wearing masks on their faces and protective gloves on their hands or while they are in quarantine to launch a barrage of satirical political jokes that It is not devoid of deep connotations that indicate a high level of social awareness and political criticism, dispelling many gaps and almost fading the existing gap between the top and the base.